Clinicopathological characteristics of localized prostate cancer in younger men aged ≤ 50 years treated with radical prostatectomy in the PSA era: A systematic review and meta‐analysis. (22nd July 2020) - Zheng, Yu; Lin, Sharron X.; Wu, Shulin; Dahl, Douglas M.; Blute, Michael L.; Zhong, Wei‐De; Zhou, Xing; Wu, Chin‐Lee
Abstract: Objectives: With the rapid increase in younger age prostate cancer (PCa) patients, the impact of younger age on decision‐making for PCa treatment needs to be revaluated in the new era. Materials and Methods: A systematic literature search was performed using PubMed, EMBASE, and Web of Science up to October 2019 to identify the eligible radical prostatectomy (RP) studies focusing on understanding the impact of age on clinicopathological features and oncological prognosis in patients with localized PCa in PSA era. Meta‐analyses were conducted using available hazard ratios (HRs) from both univariate and multivariate analyses. Results: Twenty‐six studies including 391 068 patients with RP treatments from the PSA era were included. Of these studies, age of 50 years old (age50) is the most commonly used cut‐off age to separate the younger patient group (including either age < 50 or age ≤ 50) from the older patient group. In these studies, the incidence of younger patients varied between 2.6% and 16.6% with a median of 8.3%. Younger patients consistently showed more favorable clinicopathological features correlated with better BCR prognosis. Meta‐analyses showed a 1.38‐fold improved BCR survival of younger patients in multivariate analysis. Among the high‐risk PCa patients, younger age was independently associated with worse oncological outcomes in multivariate analyses. Conclusion: In this study, we found younger age correlated with favorable clinicopathological characteristics and better BCR prognosis in low‐ to intermediate‐risk patients. In high‐risk group patients, younger patients often showed significantly worse oncological outcomes. Our study results suggest that age 50 could be used as a practical cut‐off age to separate younger age patients from older age PCa patients. Abstract : Younger age correlated with favorable clinicopathological characteristics and better BCR prognosis in low‐ to intermediate‐risk patients. In high‐risk group, younger patients often showed significantly worse oncological outcomes. Age 50 can be used as a practical cut‐off age to separate younger age patients from older age patients.